Twice Negative PCR in a Patient With Herpes Simplex Virus Type 1 (HSV-1) Encephalitis. (January 2021) - Roberts, Jodie I.; Jewett, Gordon A. E.; Tellier, Raymond; Couillard, Philippe; Peters, Steven
Untreated herpes simplex virus type 1 (HSV-1) encephalitis is associated with high mortality. Missed cases can have devastating consequences. Detection of HSV-1 in cerebrospinal fluid (CSF) with polymerase chain reaction (PCR) is reported to have high sensitivity and specificity and is considered the diagnostic gold standard for HSV-1 encephalitis. In this article, we report a case of autopsy-confirmed HSV-1 encephalitis where CSF PCR returned negative on 2 occasions. A 64-year-old man presented with fever, left-sided weakness, and altered level of consciousness. Magnetic resonance imaging demonstrated right mesial temporal lobe diffusion restriction and electroencephalography showed right lateralized periodic discharges. Lumbar puncture was performed on day 1 for which CSF PCR returned negative for HSV-1. Empiric antiviral and antibiotic treatments were continued due to high clinical suspicion of HSV-1 encephalitis. Repeat lumbar puncture on day 5 was unchanged and empiric treatments were discontinued. On day 13, he developed status epilepticus requiring intensive care unit admission. A third CSF sample returned positive for HSV-1. Acyclovir was restarted but he continued to clinically worsen and supportive care was withdrawn. Autopsy confirmed widespread HSV-1 meningoencephalitis. Negative CSF PCR should be interpreted with caution in cases where there is high clinical suspicion of HSV-1 encephalitis. Current guidelines suggest repeating CSF HSV-1 PCR within 3 to 7 days in suspicious cases while continuing empiric therapy. However, missed cases can occur even with repeated testing. Empiric treatment with acyclovir should be considered in cases with high clinical suspicion of HSV-1 encephalitis, while investigations for alternate treatable diagnoses are continued.